Effect of Coating Flour Proportion Based On Mocaf-Maizena And Frying Time On The Physical And Chemical Characteristics Of Fritter - Hermanto, Hermanto; Muhammad Iqbal Aidil Fitri YR; Gatot Priyanto (Journal of Scientech Research and Development, 2024)
This research aims to determine the effect of the proportion of coating flour and the length of frying time on the physical and chemical characteristics of fritter. Factorial randomized block design was used on parameters fat content, moisture content, and texture with two factors (A is the proportion of coating flour with three levels (100% wheat flour; 40% mocaf : 60% cornstarch; 60% mocaf : 40% cornstarch; 80% mocaf: 20% cornstarch) and B was the frying time with three levels (2 minutes; 4 minutes; 6 minutes). Non-factorial randomized block design was used for the parameters of water holding capacity and oil holding capacity with one factor (the proportion of flour) that was repeated 4 times. The results showed that the treatment of the proportion of coated flour had a significant effect on texture, moisture content, fat content, water holding capacity and oil holding capacity, while the frying time treatment had a significant effect on texture, moisture content, and fat content. The interaction between the two factors were significantly affected the texture, moisture content, and fat content. The best treatment in this research was A1B3 (mocaf 40%: cornstarch 60%; frying 6 minutes) with texture value was 1253.13 gf, moisture content was 4.59%, and fat content was 66.40% based on De Garmo test.